Efforts To Improve The Learning Outcomes of Islamic Religious Education Students with The Problem Based Learning Model at SDN 1505 Pasir Julu - Hasibuan, Sintya Lestari; Panggabean, Hotni Hairani; Sari, Ramida Purnama; Daulay, Sukria Hafifah; Daulay, Tiasma (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes in Islamic religious education learning by using the Problem Based Learning Learning Model. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. Data for this study were obtained using test and observation techniques. Tests are used to measure learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the Problem Based Learning Learning Model can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of pre-cycle 40.89%, cycle I 68.87% and in cycle II increasing to 90.32%. Thus, the Problem Based Learning Learning Model can be used as an alternative to improve student learning outcomes in Islamic religious education learning.